Promising 2,6,9-Trisubstituted Purine Derivatives for Anticancer Compounds: Synthesis, 3D-QSAR, and Preliminary Biological Assays - O Salas, Cristian; Zarate, Ana Maria; Kryštof, Vladimir; Mella, Jaime; Faundez, Mario; Brea, Jose; Loza, María Isabel; Brito, Ivan; Hendrychová, Denisa; Jorda, Radek; Cabrera, Alan R; Tapia, Ricardo A; et al. (International journal of molecular sciences, 2019)
We designed, synthesized, and evaluated novel 2,6,9-trisubstituted purine derivatives for their prospective role as antitumor compounds. Using simple and efficient methodologies, 31 compounds were obtained. We tested these compounds in vitro to draw conclusions about their cell toxicity on seven cancer cells lines and one non-neoplastic cell line. Structural requirements for antitumor activity on two different cancer cell lines were analyzed with SAR and 3D-QSAR. The 3D-QSAR models showed that steric properties could better explain the cytotoxicity of compounds than electronic properties (70% and 30% of contribution, respectively). From this analysis, we concluded that an arylpiperazinyl system connected at position 6 of the purine ring is beneficial for cytotoxic activity, while the use of bulky systems at position C-2 of the purine is not favorable. Compound 7h was found to be an effective potential agent when compared with a currently marketed drug, cisplatin, in four out of the seven cancer cell lines tested. Compound 7h showed the highest potency, unprecedented selectivity, and complied with all the Lipinski rules. Finally, it was demonstrated that 7h induced apoptosis and caused cell cycle arrest at the S-phase on HL-60 cells. Our study suggests that substitution in the purine core by arylpiperidine moiety is essential to obtain derivatives with potential anticancer activity.
Keywords: kvantitativní vztahy mezi strukturou a aktivitou; cancer; nádorové buněčné linie; apoptóza; Drug Screening Assays, Antitumor; 3D-QSAR; krystalografie rentgenová; screeningové testy protinádorových léčiv; cell cycle; Cell Line, Tumor; purine derivatives; Antineoplastic Agents; cytotoxicity; Crystallography, X-Ray; Quantitative Structure-Activity Relationship; S Phase Cell Cycle Checkpoints; Molecular Conformation; protinádorové látky; Humans; kontrolní body fáze S buněčného cyklu; molekulární konformace; Purines; puriny; apoptosis; lidé; Apoptosis